2011
DOI: 10.3945/jn.111.138875
|View full text |Cite
|
Sign up to set email alerts
|

A Sulfur Amino Acid–Free Meal Increases Plasma Lipids in Humans

Abstract: The content of sulfur amino acid (SAA) in a meal affects postprandial plasma cysteine concentrations and the redox potential of cysteine/cystine. Because such changes can affect enzyme, transporter, and receptor activities, meal content of SAA could have unrecognized effects on metabolism during the postprandial period. This pilot study used proton NMR ((1)H-NMR) spectroscopy of human plasma to test the hypothesis that dietary SAA content changes macronutrient metabolism. Healthy participants (18-36 y, 5 males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Significant changes in plasma lipid parameters (cholesterol, CHOL; triglycerides, TG; high-sensitivity C-reactive protein, hsCRP; apolipoprotein C3, apoC3) occurred in association with SAA intake [18], so we tested whether the multifractal descriptors of the plasma 1 H NMR spectra also associated with these clinical measurements. Higher values of CHOL, TG, hsCRP, and apoC3 are indicators of increased cardiovascular disease risk including, so we performed a regression analysis with a model of each of the four measurements as response, H , LS, and Std as quantitative variables and subject as a qualitative variable.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Significant changes in plasma lipid parameters (cholesterol, CHOL; triglycerides, TG; high-sensitivity C-reactive protein, hsCRP; apolipoprotein C3, apoC3) occurred in association with SAA intake [18], so we tested whether the multifractal descriptors of the plasma 1 H NMR spectra also associated with these clinical measurements. Higher values of CHOL, TG, hsCRP, and apoC3 are indicators of increased cardiovascular disease risk including, so we performed a regression analysis with a model of each of the four measurements as response, H , LS, and Std as quantitative variables and subject as a qualitative variable.…”
Section: Resultsmentioning
confidence: 99%
“…This study was performed by reanalysis of 1 H NMR spectral data from previously published studies [17], [18] that were reviewed and approved by the Emory University Investigational Review Board. The blood samples were collected with EDTA, and spectral data were generated for the different projects using procedures and settings with the intent to allow spectral data from different studies to be used for comparative analyses in a cumulative spectral database.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…No individual had the average response pattern, i.e., even though an average response was described, this average was not a good descriptor of an individual. A crossover study of sulfur amino acid insufficiency similarly showed that while about half of the individuals showed a common response pattern, no individual had an average response pattern (72). Thus, nutritional metabolomic data underscore the need to transition to complex biosystems approaches to transform nutrition to a personalized level.…”
Section: Conceptual Developmentsmentioning
confidence: 99%